Fifty years of University-industry collaboration: a global bibliometrics overview. (9th March 2021) - Bastos, Elisa Cordeiro; Sengik, Aline Rossales; Tello-Gamarra, Jorge
Abstract: This article presents a bibliometric overview of publications on university-industry collaboration (UIC) from the last fifty years (1969–2018). Among the results that were obtained, three main ones come to light. First, this article presents a complete panorama of UIC research from the past fifty years. Secondly, we were able to note that the UIC research trajectory can be divided into four generations which are represented by different phases: the discovery phase (1969–1979), the development phase (1980–1999), the expansion phase (2000–2010) and the consolidation phase (2011–2018). Furthermore, the connections and evolution pertaining to these four generations were identified. The third result was the identification of eight research trends within the UIC context: 'UIC topics' (especially: motivation, channels, barriers and results), 'engineering education', 'societies and institutions', 'knowledge transfer', 'innovation', 'entrepreneurial university', 'sustainability' and 'developing countries'.